2009
DOI: 10.1369/jhc.2009.954065
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Out of the Archive: Two-dimensional Electrophoresis and Mass Spectrometry Using HOPE-fixed, Paraffin-embedded Tissues

Abstract: Proteome analyses provide diagnostic information which can be essential for therapeutic predictions. The application of such techniques for analyzing paraffin-embedded tissue samples is widely hampered by the use of formalin fixation requiring antigen retrieval procedures in molecular pathology. In prior studies, the HEPES-glutamic acid buffer-mediated organic solvent protection effect (HOPE) technique of tissue fixation has been shown to provide a broad array of biochemical investigations with excellent prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Furthermore, a variety of commonly used ICC markers can be applied for diagnostic analysis. It was previously shown (Kähler et al 2010) that the HOPE technique allows two-dimensional separation of proteins in paraffin-embedded tissue samples, with further validation by mass spectrometry and protein Asthma 5645 643 21 6309 3989 5051 969 10,009 COPD 5895 945 10 6850 3629 4726 1800 10,155 Emphysema 3899 1158 40 5097 4418 1416 38 5872 Fibrosis 2833 687 39 3559 2644 571 56 3271 Sarcoidosis 2588 535 31 3154 2009 594 46 2649 Tuberculosis 3038 842 29 3909 2227 488 57 2772 COPD, chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, a variety of commonly used ICC markers can be applied for diagnostic analysis. It was previously shown (Kähler et al 2010) that the HOPE technique allows two-dimensional separation of proteins in paraffin-embedded tissue samples, with further validation by mass spectrometry and protein Asthma 5645 643 21 6309 3989 5051 969 10,009 COPD 5895 945 10 6850 3629 4726 1800 10,155 Emphysema 3899 1158 40 5097 4418 1416 38 5872 Fibrosis 2833 687 39 3559 2644 571 56 3271 Sarcoidosis 2588 535 31 3154 2009 594 46 2649 Tuberculosis 3038 842 29 3909 2227 488 57 2772 COPD, chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 89%
“…Fresh frozen tissue is the gold standard for such purposes, however, the preparation and storage of samples at –70 °C is elaborate, expensive and not always possible (e.g., small biopsy specimens cannot be split into two parts, and professional laboratory staff is usually not available in the evening and on weekends). Furthermore, the destruction of fine tissue morphology significantly decreases the spatial resolution, while the degradation of nucleic acids cannot be entirely avoided at long-term storage [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…18,26 The HOPE technique 10 is a preservation technique that leads to paraffin-embedded tissues without cross-linking of proteins 13 and only little degradation of nucleic acids. 11 Recently it has been shown that HOPE-fixed biomaterial allows a multitude of different molecular approaches such as 2D electrophoresis 7 or transcriptome analysis 29 out of the very same paraffin block. As the tissue processing takes 1 day longer than classical FFPE material, this might raise objections for application in routine diagnostics work-flows and therefore favors its use for biobanking or researchorientated approaches.…”
Section: Methylome and Hope Techniquementioning
confidence: 99%
“…Therefore, investigators have to face a trade-off between the applicability of different techniques with respect to both, the available amount of material and the way of tissue preservation. Recent developments have successfully demonstrated the feasibility of applying diverse techniques such as 2D proteome analysis 7 or qPCR and transcriptome analysis 8,9 from the same paraffin-embedded specimen block by application of the HOPE fixation. 10 Using HOPE for biomaterial preservation offers a multitude of read-out techniques with little nucleic acid degradation 11,12 and the possibility of immunophenotyping the sample without epitope-retrieval.…”
Section: Introductionmentioning
confidence: 99%